Pesquisa do vírus influenza HRSV e hMPV em uma população de idosos da cidade de Botucatu - São Paulo, Brasil - Watanabe, Aripuanã Sakurada Aranha [UNESP] (2006)
From about 200 virus that cause respiratory infections, only 8 are responsible for severe illness in children, immunodeficient adults and elderly, inc1uding Adenovirus, Influenza A and B, Parainfluenza 1, 2 and 3, Human RespÍratory Syncytial Vírus (HRSV) and Human Metapneumovirus (hMPV). Three of these virus are responsible for a significant morbidity in elderly: Influenza, HRSV and hMPV. The nosocomial infection caused by these vÍruses can be fatal in hospitalized children and patients with other pathologies. With the advance of the of molecular biology techniques, the diagnosis and the characterization of these vírus became more effective. Beside vírus detection by PCR, isolation of vírus in specific cellular cultures to increase the amount of pathogens have been used in severallaboratories. Studies on prevalence of respÍratory vírus in elderly are rare. The objective of this research was to evaluate the occurrence of Influenza, HRSV and of the hMPV and the risk factors involved in the diseases caused by these vÍruses. Nasopharyngeal swabs were collected and used for inoculation in cells culture and dÍrect analysis by RT-PCR. The results from RT-PCR of Influenza Vírus and RSV were negative. We also tested the samples with GeneScan, that is a technique based on fluorescent primers specific to the studied vírus. Results for Flu virus and HRSV were the same ofRT-PCR, but 1 MPV sample was positive. 55,32% ofthe 47 studied elderly were vaccinated against Influenza; 14,9% had tabagism habits and 70,2% were women. These risk factors might had influenced in the absence of positive samples for the Influenza vírus andHRSV.